MENINGKATKAN KEMAMPUAN MENULIS TEKS EKSPLANASI DENGAN MENGGUNAKAN METODE PICTURE AND PICTURE SISWA KELAS XI TEKNIK KENDARAAN RINGAN (TKR) - Luciana Ekawati; Rini Shinta Bella; Dida Firmansyah (IKIP Siliwangi, 2019)
Indonesian Language learning, especially in writing skills tends to be difficult for students, writing is considered a boring thing especially if the idea or vocabulary is very minimal, so to write text students also become confused in looking for a vocabulary or moreover ideas that must be written in the text. The difficulties of students in writing a text, moreover the explanatory text in learning Indonesian Language learned in class XI is the subject of research problems, because the results of writing explanatory texts in class XI Light Vehicle Engineering are still minimal, with the existence of the problem the researchers conduct research with the aim of increasing the ability of students to write explanatory texts, this study uses quantitative research on design One-Group pretest-posttest Design methods using picture and picture learning methods, using the method the ability of students to write explanatory texts has improved, based on initial tests and final tests that experience value change.